The Paradox of Vandalism : Fossil Fuel Dependence in Germany and International Juridical Review - Arvi Safira Febrianti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The Industrial Revolution in the late 18th to 19th century in England and Europe marked the beginning of the widespread use of fossil fuels in manufacturing, mining, and agriculture. By 2015, global fossil fuel consumption had reached 93.7 million barrels per day, with an average increase of 1.9 million barrels per year, driven by the rapid growth of the transportation and oil industries. However, 20 of the world's largest fossil fuel-producing countries, including Germany, plan to increase production by up to 110% by 2030, exceeding the limit required to restrict global warming to 1.5°C. This production level is 69% higher than needed to keep global temperatures below 2°C. These conditions have triggered protests, including acts of vandalism by the activist group